A Cooperative Clinical Trial of High-Dose Immunoglobulin Therapy in 177 Cases of Idiopathic Thrombocytopenic Purpura - Uchino, Haruto; Yasunaga, Kojiro; Akatsuka, Jun-lchi (Thrombosis and Haemostasis, 1984)
A study was conducted with the cooperation of 31 university hospitals and 44 general hospitals in Japan on high-dose immunoglobulin therapy for idiopathic thrombocytopenic purpura (ITP).Sulfonated immunoglobulins were administered to 177 patients, comprising 102 children and 75 adults for two to seven days, and a favorable rise of platelet count was found in 114 (64.4%) of these patients.In particular, of the 107 patients who had not responded favorably to adrenocortico-steroids therapy, 63 cases showed a favorable rise of platelet count. And of the 14 patients who had not responded favorably to splenectomy, 6 cases showed a favorable rise of platelet count.In the majority of cases the platelet count fell to its pretreatment level within one month after the start of sequence of administration.Although a dosage of 400 mg/kg/day was suitable for most patients, the wide range of individual responses suggested the desirability of determining an optimal dose for each patients.
Keywords: Immunoglobulin therapy; S-sulfonated gammaglobulin; Idiopathic thrombocytopenic purpura